Origins of the Photobooth in Spain (1888-1929) - Vega Pérez, Celia (Revista General de Información y Documentación, 2014)
In the 1888 Barcelona Universal Exposition, Juan Cantó showed, for the first time in Spain, his automatic photography machine, a precedent of the photobooth. Since the until 1929, the date on which the first Photomaton studio was open and the first Fotodin devices were installed, different models of automatic photography machines were patented in Spain. This study reviews the history of the early years of the booth and its antecedents through patents of automatic photography apparatus between 1888 and 1929, and the pioneering companies in the exploitation, sale and rental of these devices.